Impact of the needle winding technology on the operational behavior of an asynchronous machine - Stenzel, P.; Richnow, J.; Franke, Jörg; Endisch, C. (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
Distributed round-wire windings are usually manufactured using the insertion technology. If the needle winding technology is applied instead the end windings have to be conducted in a three-layer axial arrangement. This leads to differing coil lengths and thus to a phase asymmetry which is much more distinct than the one resulting from the insertion technology. In addition, it is possible that the first phase exhibits a higher end winding leakage inductance than the other phases if the distance between the first phase and the front end side of the stator core is too short. In this case the magnetic flux lines of the end windings partially close across the stator core producing an increase of the end winding leakage inductance. Therefore, in this paper the impact of the needle winding technology on the operational behavior of an asynchronous machine is investigated. For this purpose a needle wound electrical machine with three-layer end windings is compared to an electrical machine with very symmetric windings built up using manual insertion. By the use of the no load and blocked rotor test as well as a static stator measurement the machine parameters are determined and the impact of the phase asymmetry is investigated. In addition, load measurements are conducted in order to quantify the impact of the production related differences.
CRIS-Team Scopus Importer:2023-03-07